Correlation of urinary mcp-1 and tweak with renal histology and early response to therapy in newly biopsied patients with lupus nephritis in cape town, South Africa - Moloi, Mothusi Walter (Department of Medicine, 2020)
Background: There is need for judicious use of immunosuppression in patients with active lupus nephritis (LN), however this is guided by renal biopsy which is invasive and not freely available in most centres. Novel urinary biomarkers such as monocyte chemoattractant protein-1 (MCP-1) and tumour necrosis factor-like weak inducer of apoptosis (TWEAK) are secreted in the kidney and may be useful for predicting histological class, monitoring flares and assessing response to therapy. We assessed the utility of urinary MCP-1 (uMCP-1) and TWEAK (uTWEAK) in predicting renal histological findings, disease flares and treatment response 6 months following initiation of treatment for LN in newly biopsied patients. Methods: We recruited consenting patients with active LN confirmed on kidney biopsy. Relevant baseline demographic, biochemical and histological information was collected from the patients. ELISA methods were used to assess uMCP-1 and uTWEAK at baseline and at 6 months after completion of induction therapy. Results: There were 14 females and 6 male patients with a mean age of 29.8 ± 10.7 years, 60% were of mixed ancestry, 70% had proliferative LN. There was no association between uMCP-1 and uTWEAK and histological features (LN class, activity index, chronicity index and interstitial fibrosis). At 6 months, 6 patients were lost to follow-up and of the remaining 14, 12 (85%) attained remission (partial remission (n = 7) or complete remission (n = 5)). Both biomarkers were elevated in patients with active disease and significantly declined amongst those attaining remission, p = 0.018 and p = 0.015 respectively. However, for those not attaining remission, no association was found for both biomarkers (p >0.05). Conclusion: Our study did not show correlation between uMCP-1 and uTWEAK with histological features of LN. However, both biomarkers were elevated in patients with active disease and correlated with the remission status at the end of induction phase of treatment.